If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7x = 11 Combine like terms: 5x + -7x = -2x -2x = 11 Solving -2x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = -5.5 Simplifying x = -5.5
| -2(7x+9)=-11 | | X+(X*0.2)=91000000 | | 3z-8=7[z-3] | | x=0.89 | | X+15=95 | | 2(-6x+6)=96 | | X+(X*0.2)=101167200 | | 6x^2-13xy-28y^2=0 | | X+(X*0.2)=12 | | y=0.18x^3-2.16x^2+4.86x | | t+7-13=-4 | | sin(3x-30)=0.6 | | 4A-20=22 | | -6(7+X)=-42 | | 7.3+z=60 | | 10a+15b=2x | | 2x+10=-3x | | 2x+5*3=11 | | 2ln(2*x+1)-3ln(x+1)+ln(x+1)=0 | | 3x+18=3x+34 | | 2(4-5x)=7-5(x-2) | | 20+1d=30+.5d | | 4n+3m=11 | | -30=5w+5 | | 64=9u-u | | 103+5x=63 | | 2(x)=54 | | x/-6=120 | | 2y+16=48 | | 2x-2-3=21-34x | | 31+4x=86 | | xln(x)-1=0 |